Anthropology of Performance or Anthropology of Contemporary Theatre?: ethnographic remarks on companhia brasileira de teatro and PROJETO bRASIL - Kruger, Cauê (Revista Brasileira de Estudos da Presença, 2021)
Based on anthropological and ethnographical fieldwork research with companhia brasileira de teatro this article points to some limits of a universalist and orthodox anthropology of performance. It sustains, alternatively, one anthropology of contemporary theatre, dealing with concepts such as drama, performance and dramaturgy as research realms, able to express desires, expectancies, and meanings disputes enrolled in the artistic process. This study reveals how performative theatre, metadiscursive and de-dramatizing strategies lead to polysemic and reflexive scenes that provide critical discourses, viewpoints shifts and encourage sensibility for alterity.